ChemInform Abstract: Copper(II)‐Triflate‐Catalyzed Oxidative Amidation of Terminal Alkynes: A General Approach to α‐Ketoamides. Issue 49 (December 2015) - Kumar, Manjeet; Devari, Shekaraiah; Kumar, Arvind; Sultan, Shaista; Ahmed, Qazi Naveed; Rizvi, Masood; Shah, Bhahwal Ali
Abstract: In the presence of atmospheric oxygen, secondary and primary amines can be used in the title process.